Sponge derived-Aspergillus as a promising source of antimicrobial compounds: a literature review - Erlina, Ni Putu Natasha Ernianti; Wulandari, Ni Made Widya; Dwijayanti, Ni Kadek; Ariantari, Ni Putu (Jurnal Biologi Udayana, 2025)
develop the ability to survive upon exposure to the existing antibiotics. This situation results in a decrease in the effectiveness of drugs used to treat infections. Fungi associated with marine sponges are a potential source of bioactive compounds with various biological activities, including antimicrobial properties. These microorganisms can adapt to extreme conditions and produce a wide array of chemical compounds. Among these fungi, Aspergillus is one of the most commonly found genera associated with marine sponges. The bioactive compounds produced by this fungus are known to exhibit antimicrobial activity against various pathogens. This review aims to examine the diversity of chemical compounds produced by Aspergillus isolated from marine sponges and their antimicrobial activity, based on data from scientific literature over the past 10 years (2014–2024). The databases used in this review include PubMed, ScienceDirect, and Google Scholar. Sixteen species of Aspergillus derived from marine sponges have been identified by far. These species were reported for their capability for producing more than 100 compounds, including alkaloids, sesquiterpenes, isocoumarins, terpenoids, and polyketide compounds. Among them, around 50 compounds demonstrated antimicrobial activity against various pathogens, including strains resistant to current antibiotics.